TINJAUAN HADITS TENTANG PERAN LINGKUNGAN DALAM PROSES PENDIDIKAN: Hadits; Tarbawi; Lingkungan; Proses Pendidikan - Windy Nur Dwi Maharani; Anita, Anita Prita Cinta; Ilham Jaelani; Ramdhani, Muhammad Rendi (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2025)
The environment plays a crucial role in the educational journey, particularly in shaping students' character and moral values. From an Islamic perspective, education goes beyond the mere transfer of knowledge; it encompasses character building through exemplary behavior and consistent practice within a supportive environment. This study explores how environmental factors influence education based on the hadith of the Prophet Muhammad (peace be upon him), focusing on the family and social context. Using qualitative literature research methods, the study collected and analyzed descriptive data from various Islamic and educational sources. The results highlight the family as the primary foundation for instilling faith and moral integrity, while the broader social environment shapes behavior through routine interactions. The hadiths examined highlight the importance of selecting a positive environment as a vehicle for education. The study concludes that the effectiveness of Islamic education is closely linked to the quality of the surrounding environment. This demonstrates the importance of synergy between families, educational institutions, and the wider community in